Breast cancer extracellular vesicles-derived miR-1290 activates astrocytes in the brain metastatic microenvironment via the FOXA2→CNTF axis to promote progression of brain metastases. (1st August 2022) - Sirkisoon, Sherona R.; Wong, Grace L.; Aguayo, Noah R.; Doheny, Daniel L.; Zhu, Dongqin; Regua, Angelina T.; Arrigo, Austin; Manore, Sara G.; Wagner, Calvin; Thomas, Alexandra; Singh, Ravi; Xing, Fei; et al.
Abstract: Mechanisms underlying breast cancer brain metastasis (BCBM) are still unclear. In this study, we observed that extracellular vesicles (EVs) secreted from breast cancer cells with increased expression of tGLI1, a BCBM-promoting transcription factor, strongly activated astrocytes. EV-derived microRNA/miRNA microarray revealed tGLI1-positive breast cancer cells highly secreted miR-1290 and miR-1246 encapsulated in EVs. Genetic knockin/knockout studies established a direct link between tGLI1 and both miRNAs. Datamining and analysis of patient samples revealed that BCBM patients had more circulating EV-miRs-1290/1246 than those without metastasis. Ectopic expression of miR-1290 or miR-1246 strongly activated astrocytes whereas their inhibitors abrogated the effect. Conditioned media from miR-1290- or miR-1246-overexpressing astrocytes promoted mammospheres. Furthermore, miRs-1290/1246 suppressed expression of FOXA2 transcription repressor, leading to CNTF cytokine secretion and subsequent activation of astrocytes. Finally, we conducted a mouse study to demonstrate that astrocytes overexpressing miR-1290, but not miR-1246, enhanced intracranial colonization and growth of breast cancer cells. Collectively, our findings demonstrate, for the first time, that breast cancer EV-derived miR-1290 and miR-1246 activate astrocytes in the brain metastatic microenvironment and that EV-derived miR-1290 promotes progression of brain metastases through the novel EV-miR-1290→FOXA2→CNTF signaling axis. Highlights: tGLI1-positive breast cancer cells secrete high levels of EV-miR-1290 and miR-1246 that strongly activate astrocytes. BCBM patients have more circulating EV-miRs-1290/1246 than those without metastasis. miR-1290 or miR-1246 strongly activate astrocytes; miR-1290- or miR-1246-overexpressing astrocytes promote mammospheres. miRs-1290/1246 suppress expression of transcriptional repressor FOXA2, leading to CNTF secretion and astrocyte activation. Astrocytes overexpressing miR-1290, but not miR-1246, enhance intracranial colonization and growth of breast cancer cells.